(untitled) (Bangladesh Journal of Botany, 2014)
Several varietal screening methods were tested along with dipping dry seeds into millipore membrane filtrate of spore suspension of the pathogen and gibberellic acid (GA3) in different concentrations. It was found that GA3 can be used to screen out susceptible rice varieties against bakanae disease. The method which requires the use of GA3 is easier than the other methods for mass screening as it does not require maintaining living culture of the pathogen. The protocol of inoculum free varietal screening method for bakanae disease of rice was developed to find out resistant varieties from the huge collections of germplasm bank. DOI: http://dx.doi.org/10.3329/bjb.v42i2.18036 Bangladesh J. Bot. 42(2): 315-320, 2013 (December)